2002
DOI: 10.1021/la0110592
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Aggregation Behavior of 15 Polymeric and Monomeric Dipeptide Surfactants in Aqueous Solution

Abstract: The aggregation numbers of 15 dipeptide surfactants were estimated by use of fluorescence steady-state quenching techniques. Polymerization of the surfactants with γ radiation resulted in molecular micelles with a lower number of repeat units than the corresponding monomer aggregation numbers at the concentration of monomer used for polymerization in this study. In addition, the aggregation numbers of the monomers decreased with increasing size of the N-terminal R group of the dipeptide surfactants examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
1
34
1
Order By: Relevance
“…The A value of conventional micelles of SUG and SUCG was found to be significantly higher than the corresponding A value of micelle polymers, which is consistent with previous observations [36]. Furthermore, from the comparison of aggregation data for both SUG and SUCG surfactants, it can be argued that the carbamate group of SUCG surfactant series occupies a more compact space as compared to the amide group of SUG surfactants.…”
Section: Effect Of the Polar Head Group On Aggregation Number Of Monosupporting
confidence: 88%
“…The A value of conventional micelles of SUG and SUCG was found to be significantly higher than the corresponding A value of micelle polymers, which is consistent with previous observations [36]. Furthermore, from the comparison of aggregation data for both SUG and SUCG surfactants, it can be argued that the carbamate group of SUCG surfactant series occupies a more compact space as compared to the amide group of SUG surfactants.…”
Section: Effect Of the Polar Head Group On Aggregation Number Of Monosupporting
confidence: 88%
“…From the analytical ultracentrifugation measurements, the weight-average molecular weight for the polymeric surfactant poly-L-SOLV, was calculated and found to be 36 102 6 948. Using this weightaverage molecular weight, the aggregation number of the polymer poly-L-SOLV was determined to be 69 which correlates well with the polymer's aggregation number obtained by use of a Spex FluoroMax-3 spectrofluorimeter at room temperature using the fluorescence quenching method described by Billiot et al [39] (data not shown). Figure 4 illustrates the equilibrium distribution of poly-L-SOLV at 257C.…”
Section: Determination Of the Molecular Weight Of Poly-l-solvmentioning
confidence: 99%
“…Steady-state fluorescence quenching techniques were used to determine that the degree of polymerization for 15 polymeric chiral surfactants (18)(19)(20)(21)(22)(23)(24)(25) was one-half to one third of the aggregation number of the corresponding monomers (38-74) [38]. Five of the monomers had very high aggregation numbers (110-380), but the degree of polymerization of the corresponding polymers was not different from the other polymers.…”
Section: Polymerized Amino Acid Surfactantsmentioning
confidence: 99%